A rare presentation of orbital complication of invasive fungal sinusitis in an immunocompetent young boy-a rare case - Gaur, S; Lavania, A; Saxena, R (Journal of College of Medical Sciences-Nepal, 2012)
We present a case of allergic fungal sinusitis (AFS) in a 24 -year old man with history of left sided nasal obstruction and discharge since few years. Since few months he developed epiphora in the left eye associated with discomfort on eye movements. Patient was examined and CT with contrast was done. CT contrast showed an enhancing lesion in Left maxillary and ethmoid sinuses and erosion of the inferior bony wall of the orbit and medial wall of maxillary sinus. Though most patients of fungal sinusitis are immunocompromised but this patient was young male immunocompetent and made an unusual presentation with visual epiphora and painful eye movements. CT showed bony erosion of the Left inferior Bony wall of the Orbit and medial wall of Maxillary Sinus. After through examination and specific investigations, the patient was posted for surgery. We planed for Cald well –Luc’s Surgery and Endoscopic excision of the mass .Histological examination was reported as non malignant and microscopy showed Fungal Hyphae. After the surgery patient was discharged satisfactorily within couple of days and followed up regularly. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-1, 48-51 DOI: http://dx.doi.org/10.3126/jcmsn.v8i1.6826